Remoteness promotes biological invasions on islands worldwide - Moser, Dietmar; Lenzner, Bernd; Weigelt, Patrick; Dawson, Wayne; Kreft, Holger; Pergl, Jan; Pyšek, Petr; van Kleunen, Mark; Winter, Marten; Capinha, César; Cassey, Phillip; Dullinger, Stefan; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
One of the best-known general patterns in island biogeography is the species-isolation relationship (SIR), a decrease in the number of native species with increasing island isolation that is linked to lower rates of natural dispersal and colonization on remote oceanic islands. However, during recent centuries, the anthropogenic introduction of alien species has increasingly gained importance and altered the composition and richness of island species pools. We analyzed a large dataset for alien and native plants, ants, reptiles, mammals, and birds on 257 (sub) tropical islands, and showed that, except for birds, the number of naturalized alien species increases with isolation for all taxa, a pattern that is opposite to the negative SIR of native species. We argue that the reversal of the SIR for alien species is driven by an increase in island invasibility due to reduced diversity and increased ecological naiveté of native biota on the more remote islands.
Keywords: ostrovy; island invasibility; tropické klima; biologické modely; Models, Biological; Islands; Tropical Climate; Introduced Species; naturalization; zavlečené druhy; island biogeography; alien species; isolation